Adhesive for food packaging and application thereof
By grafting 3-isocyanate propyltrimethoxysilane onto the hydroxylated spherical alumina surface in the food packaging adhesive, and combining it with isocyanate small molecules and polyols to form a crosslinked structure, the shortcomings of the existing adhesive in terms of bonding strength, debonding performance and barrier properties are solved, high oxygen barrier and oil resistance are achieved, and the performance of food packaging materials is improved.
Patent Information
- Application Number
- CN202510139893.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-02-08
AI Technical Summary
The existing food packaging adhesives have shortcomings in bonding strength, debonding performance and barrier properties, and it is difficult to meet the requirements of food safety and packaging strength.
By grafting 3-isocyanate propyltrimethoxysilane onto the hydroxylated spherical alumina surface, doping it with different types of isocyanate small molecules, combining polyols as soft segments, adjusting the ratio of hard segments to soft segments, forming a crosslinking structure, a polyurethane adhesive with excellent bonding strength, debonding characteristics and oxygen barrier properties was prepared.
This adhesive not only performs excellently in terms of bonding strength and debonding performance, but also has high oxygen barrier properties, which can meet the requirements of food packaging for oil resistance and aging resistance, and improve the overall performance of food packaging materials.
Smart Images

Figure CN119614134A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of adhesives for food packaging films, in particular to an adhesive for food packaging and application thereof. Background Art
[0002] As an important part of the food industry, food packaging not only needs to ensure that the packaging materials have sufficient strength, durability and sealing properties, but also requires that they can effectively improve the gas barrier properties of the packaging film, especially the oxygen barrier properties, which are crucial to extending the shelf life of food. Therefore, the adhesion and gas barrier properties of food packaging materials directly affect the packaging quality and the preservation effect of food.
[0003] Traditional food packaging adhesives are mostly solvent-based adhesives or hot melt adhesives, which have certain problems in environmental adaptability, durability and health safety, such as the release of harmful gases during the curing process and poor adaptability to various materials. Therefore, the development of a polyurethane adhesive with excellent bonding strength, good debonding properties, high barrier, environmental friendliness and wide adaptability is of great significance for improving the performance and safety of food packaging materials.
[0004] Polyurethane adhesives are widely used in various industrial fields due to their adjustable hard segment to soft segment ratio, excellent adhesion and toughness, but their application in the field of food packaging still faces the challenge of how to optimize their performance to meet food safety and packaging strength. In the existing technology, although polyurethane adhesives are used in packaging, they still need to be further optimized and improved in terms of the unique requirements of food packaging (such as oil resistance, debonding and barrier properties, etc.). Summary of the invention
[0005] In order to overcome the deficiencies of existing food packaging adhesives in terms of bonding strength, debonding performance and barrier performance, the present invention provides a polyurethane adhesive for food packaging and its application. The adhesive not only has excellent bonding strength and debonding performance, can meet the requirements of various environmental conditions such as oil resistance and aging resistance in food packaging, but also has high oxygen barrier performance, thereby improving the overall performance of food packaging materials.
[0006] The technical scheme adopted by the present invention is: by grafting 3-isocyanate propyl trimethoxy silane on the surface of hydroxyl-rich spherical alumina, doping with different types of isocyanate small molecules (such as hexamethylene diisocyanate, toluene diisocyanate, etc.) as hard ends, selecting polyols containing active hydrogen (such as polyethylene glycol, polyoxypropylene glycol, polycaprolactone, etc.) as soft segments, further adjusting the ratio of soft and hard segments, enhancing the bonding force between the hard segment and the soft segment of the adhesive, and reacting to form a cross-linked structure to obtain ideal adhesive performance. Through this optimized formula, the adhesive of the present invention has high bonding strength, debonding characteristics and oxygen barrier properties, and can be widely used in the bonding of food packaging materials.
[0007] The invention provides an adhesive for food packaging, which comprises polyurethane. The polyurethane is prepared by the following method: a polyol, a polyester and an isocyanate component are mixed to undergo a polymerization reaction, wherein the isocyanate component comprises hydroxylated spherical alumina grafted with isocyanate groups.
[0008] In the present invention, the hydroxyl-rich spherical alumina grafted with isocyanate groups is hydroxyl-rich spherical alumina grafted with 3-isocyanate propyltrimethoxysilane.
[0009] In the present invention, the hydroxyl-rich spherical alumina grafted with isocyanate groups can be prepared by the following method: (1) treating the spherical alumina with an alkali to obtain the hydroxyl-rich spherical alumina; preferably, the alkali is NaOH or KOH.
[0010] (2) reacting hydroxyl-rich spherical alumina with silyl-containing isocyanate to obtain hydroxyl-rich spherical alumina grafted with isocyanate groups; preferably, the silyl-containing isocyanate is 3-isocyanatepropyltrimethoxysilane.
[0011] In the present invention, the polyurethane may further contain a catalyst, and the catalyst is dimethylnitrosamine.
[0012] In the present invention, the polyol is polyethylene glycol.
[0013] In the present invention, the polyester is polycaprolactone.
[0014] In the present invention, the isocyanate component is one or more of hexamethylene diisocyanate, toluene diisocyanate and hydroxyl-rich spherical alumina grafted with isocyanate groups.
[0015] In the present invention, the isocyanate component is a mixture of hexamethylene diisocyanate, toluene diisocyanate and hydroxylated spherical alumina grafted with isocyanate groups.
[0016] In the present invention, in the mixture, the mass ratio of the isocyanate components hexamethylene diisocyanate, toluene diisocyanate and hydroxylated spherical alumina grafted with isocyanate groups is (3-7): (3-7): 0.5; preferably 5:5:0.5.
[0017] In the present invention, the mass ratio of the polyol, the polyester and the isocyanate component is 10:(4-6):(0.8-1.2); preferably 10:5:1.
[0018] The present invention also provides a method for preparing an adhesive for food packaging, which comprises the following steps: dissolving the polyurethane in a solvent to obtain the adhesive for food packaging, preferably, the solvent is ethyl acetate.
[0019] In the present invention, in the adhesive for food packaging, the solid content of the adhesive is 20-70% by weight, preferably 50% by weight.
[0020] The present invention also provides a use of the adhesive for food packaging in a food packaging bag.
[0021] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0022] The reagents and raw materials used in the present invention are commercially available.
[0023] The positive and progressive effects of the present invention are: (1) by introducing new hard end materials and adjusting the ratio of hard segments to soft segments, the initial bonding strength of the adhesive is optimized.
[0024] (2) The adhesive's anti-aging, oil resistance and other stability in harsh environments are enhanced, ensuring operability in practical applications without affecting the bonding strength of packaging materials.
[0025] (3) It adopts an environmentally friendly and safe formula that meets food safety requirements, is not prone to side reactions during the curing process, is easy to operate, and has better stability. This adhesive not only improves the overall performance of food packaging, but also has good market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 FT-IR spectrum of hydroxylated spherical alumina.
[0027] Figure 2 This is the FT-IR spectrum of spherical alumina grafted with 3-isocyanatepropyltrimethoxysilane and enriched in hydroxyl groups. DETAILED DESCRIPTION
[0028] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0029] The present invention further relates to an adhesive composition according to the present invention for use in an adhesive for food packaging films.The present invention will be explained in more detail with reference to the following examples, which are not intended to limit the inventive concept.
[0030] General method for preparing adhesive: Step 1, prepare hydroxyl-rich spherical alumina.
[0031] This step aims to introduce hydroxyl groups into the surface of spherical alumina through hydroxyl enrichment treatment to improve its binding ability with 3-isocyanatepropyltrimethoxysilane, thereby enhancing the cross-linking effect between the hard segment and the soft segment of the adhesive.
[0032] (1) Cleaning the surface of alumina: Add spherical alumina (10 g, particle size: 0.2 μm) to 500 mL of deionized water and stir thoroughly to clean impurities. Filter out the alumina by vacuum filtration and rinse with deionized water several times until no obvious impurities appear in the filtrate. Place the cleaned spherical alumina in an oven and dry it at 120°C for 12 hours until it is completely dry to obtain dry spherical alumina.
[0033] (2) Surface hydroxylation treatment: Take 2 g of sodium hydroxide and add it to 100 mL of deionized water, stir and dissolve to obtain a sodium hydroxide solution with a concentration of 2% (w / v). Add the cleaned and dried spherical alumina (10 g) to a 500 mL beaker and add 200 mL of 2% sodium hydroxide solution. Place the beaker on a hot plate, heat it to 60°C, and stir and react at this temperature for 4 hours to ensure that the sodium hydroxide solution is in full contact with the surface of the alumina. During the reaction, the alkaline conditions of sodium hydroxide cause a large number of hydroxyl (OH) groups to form on the surface of the alumina, increasing the surface hydrophilicity.
[0034] (3) Neutralization and washing: After the reaction is completed, the reaction solution is cooled to room temperature and slowly neutralized to neutrality (pH = 7) using dilute sulfuric acid (concentration of about 1 M). This step can remove excess sodium hydroxide and further enhance the stability of the hydroxyl groups on the surface of alumina. After neutralization, the spherical alumina is separated by vacuum filtration and thoroughly washed with deionized water until the pH value of the filtrate is close to 7. The washed alumina is further washed with ethanol for 3 times to remove residual moisture and impurities.
[0035] (4) Drying and characterization: The washed hydroxyl-rich spherical alumina was placed in an oven and dried at 80°C for 12 hours to obtain hydroxyl-rich spherical alumina powder. The surface of the hydroxyl-rich alumina was characterized by Fourier transform infrared spectroscopy (FT-IR) analysis to observe whether there was a hydroxyl characteristic peak (about 3200 cm -1 ) and other possible surface changes.
[0036] Through the above steps, the hydroxylation treatment of spherical alumina was successfully achieved. A large number of hydroxyl groups were introduced on the surface, which enhanced its hydrophilicity and reactivity with isocyanate groups. The 3200 cm -1 The characteristic peaks of hydroxyl groups on the surface of the alumina were observed, proving that the surface was successfully enriched with hydroxyl groups. The treated spherical alumina can provide a good reaction basis for the subsequent silane grafting reaction, thereby improving the performance of the polyurethane adhesive.
[0037] Step 2: prepare spherical alumina grafted with 3-isocyanatepropyltrimethoxysilane and enriched in hydroxyl groups.
[0038] The purpose of this step is to react hydroxyl-rich spherical alumina with 3-isocyanatepropyltrimethoxysilane (A-1120) to graft isocyanate groups on the surface of alumina to enhance its bonding with the polyurethane hard segment and further improve the performance of the adhesive.
[0039] (1) Activation of alumina surface: Place hydroxylated spherical alumina (10 g, prepared in step 1) in a 50 mL dry round-bottom flask and add 30 mL of anhydrous ethanol. Add 5 mL of deionized water to the flask and stir evenly to activate the hydroxyl groups on the surface of alumina, making it more active and easier to react with 3-isocyanatepropyltrimethoxysilane.
[0040] (2) Grafting reaction: Add 3-isocyanate propyl trimethoxysilane (A-1120, 5 g) to the above-mentioned alumina-ethanol-water mixed solution and stir evenly. The reaction mixture is stirred at 60°C for 4 hours. During the reaction, the ethoxy group of 3-isocyanate propyl trimethoxysilane reacts with the hydroxyl group on the surface of alumina to form a siloxane bond (Si-O-Al).
[0041] (3) Post-reaction treatment: After the reaction is completed, the reaction mixture is cooled to room temperature. The reaction product is washed with deionized water and ethanol several times to remove unreacted silane and solvent. After filtration, the grafted alumina is dried in an oven at 80°C for 12 hours until a dry grafted alumina powder is obtained.
[0042] (4) Characterization and analysis: Fourier transform infrared spectroscopy (FT-IR) was used to characterize the grafted alumina. Analyze whether 3-isocyanate propyltrimethoxysilane was successfully grafted. The characteristic peak of the grafted isocyanate group appears at 2270 cm -1 nearby.
[0043] Through the above steps, 3-isocyanatepropyltrimethoxysilane was successfully grafted onto the surface of hydroxyl-rich spherical alumina. The FT-IR spectrum showed that the -1 An obvious characteristic peak of isocyanate group appeared at the bottom, indicating that the grafting reaction was successful.
[0044] Step 3: prepare the adhesive.
[0045] This embodiment aims to prepare a polyurethane adhesive with excellent performance by dispersing and doping grafted aluminum oxide with different types of isocyanates and polymerizing them with polyols. The adhesive has high bonding strength and good flexibility and can be widely used in the bonding of food packaging materials.
[0046] (1) Prepare the adhesive raw material mixture: Take 0.5 g of spherical alumina grafted with 3-isocyanate propyltrimethoxysilane and hydroxylated (prepared in step 2) and add it to a 250 mL flask, add 30 mL of toluene, and stir evenly to ensure that the grafted alumina is evenly dispersed in the solvent. At the same time, weigh a total of 10 g of hexamethylene diisocyanate (HDI) and toluene diisocyanate (TDI) in different mass proportions and add them to two different flasks respectively, and add 10 mL of toluene to dissolve them completely. Then, mix the HDI and TDI solutions in proportion to obtain a mixed isocyanate solution.
[0047] (2) Isocyanate dispersion doping: Slowly add the mixed isocyanate solution to the grafted alumina dispersion and stir evenly. Control the temperature at around 30°C and keep stirring for about 30 minutes to ensure that the isocyanate molecules are evenly dispersed on the grafted alumina surface. Transfer the above mixture to an oven and dry it at 80°C for 12 hours to remove excess solvent toluene to obtain grafted alumina powder doped with isocyanate.
[0048] (3) Preparation of polyurethane adhesive by polymerization reaction: In a 250 mL flask, take 10 g of polyethylene glycol (PEG-2000) and 5 g of polycaprolactone (PCL-1000), add 60 mL of toluene, and stir evenly until dissolved. This step can effectively ensure that the polyol is fully dissolved in the solvent and provide a uniform reaction environment for the polymerization reaction. Heat the above solution to 70°C, add 0.2 g of dimethylnitrosamine (DMAPA) as a catalyst, and continue stirring for 30 minutes to ensure the activation of the polyol mixture. Slowly add grafted alumina powder doped with isocyanate (1 g) and continue stirring to react. At this time, a polymerization reaction will occur between the isocyanate group and the polyol to form a polyurethane skeleton. During the reaction, the isocyanate group reacts with the hydroxyl groups in polyethylene glycol and polycaprolactone to form a polyurethane chain. The reaction lasts for 2 hours at 70°C to ensure the completion of the polymerization reaction.
[0049] (4) Removal of solvent and preparation of final product: After the reaction is completed, the reaction system is cooled to room temperature, and the reaction product is washed with deionized water to remove the residual catalyst, solvent and unreacted raw materials. Then, the adhesive solution is transferred to an oven and dried at 80°C for 12 hours, and then ethyl acetate is added to prepare an adhesive solution with a solid content of 50% by weight, thereby obtaining a polyurethane adhesive product.
[0050] Example 1: Adhesive sample A: According to the general method for preparing an adhesive, HDI and TDI are mixed in a ratio of 1:1, the temperature is 70° C., and the reaction time is 2 hours to prepare an adhesive.
[0051] Example 2: Adhesive sample B: According to the general method for preparing an adhesive, the ratio of HDI to TDI was adjusted to 1:2, and the reaction temperature was increased to 80° C.; the reaction time was 2 hours, and the adhesive was prepared.
[0052] Example 3: Adhesive sample C: According to the general method for preparing an adhesive, the reaction time was extended to 3 hours, the temperature was maintained at 70°C, and the ratio of HDI to TDI was maintained at 1:1; the adhesive was prepared.
[0053] Adhesive 4: Adhesive Sample D: The adhesive was prepared according to the general method for preparing adhesives, except that the reaction time was shortened to 1 hour, the temperature was maintained at 70°C, and the ratio of HDI to TDI was maintained at 1:1.
[0054] Example 5: Adhesive Sample E: According to the general method for preparing an adhesive, the reaction time was shortened to 1 hour, the temperature was maintained at 70°C, and the ratio of HDI to TDI was maintained at 2:1; the adhesive was prepared.
[0055] Example 6: Adhesive Sample F: According to the general method for preparing an adhesive, the reaction time was extended to 3 hours, the temperature was maintained at 70°C, and the ratio of HDI to TDI was maintained at 2:1; the adhesive was prepared.
[0056] Example 7: Adhesive Sample G: According to the general method for preparing an adhesive, but without using the spherical alumina raw material enriched with hydroxyl group grafted with 3-isocyanatepropyltrimethoxysilane, HDI and TDI were mixed in a ratio of 1:1, the temperature was 70°C, and the reaction time was 2 hours to prepare an adhesive.
[0057] Effect embodiment: Performance test of adhesives prepared under different conditions.
[0058] This example evaluates the bonding performance of adhesives prepared under different conditions by conducting comprehensive performance tests. The following aspects are mainly examined: viscosity of the adhesive solution, bonding strength, initial adhesion after aging, peel strength after sterilization, and content resistance. The samples selected in this example are representative samples and do not limit the sample preparation conditions of the present invention.
[0059] Materials and reagents: Test substrates: aluminum foil (domestic, thickness 50 μm), polyethylene terephthalate (PET) film (domestic, thickness 100 μm), cast polypropylene (CPP) film (domestic, thickness 80 μm).
[0060] Reagents and solvents: deionized water, ethanol, toluene.
[0061] Testing equipment and tools: rotational viscometer (Brookfield, DV-II), tensile testing machine (Instron, 5965), oxygen permeability tester (MOCON, OX-TRAN 2 / 40), water vapor permeability tester (MOCON, AQUATRAN 3 / 40), oven, constant temperature and humidity chamber, titration bottle, UV sterilizer (UltraClean 1000).
[0062] (1) Preparation of adhesive samples: The preparation methods of samples A, B, C, D, E, F and G refer to the steps in Example 3, except that the ratio of HDI to TDI, reaction temperature and reaction time are adjusted under different reaction conditions. Ensure that each sample can obtain a sufficient degree of curing and that the solvent and unreacted components are completely removed.
[0063] (2) Preparation of food packaging film samples: First, the adhesive was evenly coated on the surface of the PET and CPP films, and the coating amount of the solid component was adjusted to 4 g / m². Subsequently, the PET and CPP films coated with the adhesive were dried at 80°C for 10 minutes to obtain the adhesive-coated PET and CPP films. Next, the dark side of the aluminum foil was covered on the surface of the adhesive-coated PET film, and the bright side of the aluminum foil was covered on the surface of the adhesive-coated CPP film; and the two layers of film were pressed together for 30 minutes using a flat press at 50°C and a closed pressure of 1.0 MPa. Finally, the pressed film was aged at 50°C for 3 days to obtain the final food packaging film sample.
[0064] (3) Adhesive performance test: ① Adhesive solution viscosity test: A rotational viscometer (Brookfield, DV-II) was used to measure the viscosity of each adhesive solution. The test conditions were as follows: measurement temperature: 25°C, rotation speed: 10 rpm, sample volume: 2 mL.
[0065] ② Adhesion strength test: The adhesion strength of different adhesive samples was tested using a tensile testing machine. The food packaging films prepared with different adhesives were cut into 15 mm wide test pieces and subjected to a 90° tensile peel test. The test conditions were as follows: test speed: 300 mm / min, test temperature: 25°C (room temperature). The maximum tensile strength was recorded.
[0066] ③ Initial adhesion test after aging: Food packaging films prepared with different adhesive samples were cut into 15 mm wide test pieces and placed in an oven at 60°C for aging for 48 hours. Then, the initial adhesion after aging was evaluated. The test method was as follows: The bonding strength of the adhesive to the PET film and aluminum foil after aging was measured using a tensile testing machine. The initial peel strength was recorded using a peel test (tensile speed: 300 mm / min).
[0067] ④ Peel strength test after sterilization: The food packaging films prepared with different adhesive samples were placed in a UV sterilizer for sterilization. The sterilization conditions were: UV wavelength 254 nm, sterilization time 30 minutes. After sterilization, the peel strength of the adhesive was evaluated by a peel test (tensile speed: 300 mm / min).
[0068] ⑤ Oxygen barrier performance (oxygen permeability) test: Food packaging films prepared with different adhesive samples were cut into 15 mm wide samples and the oxygen permeability was tested using the constant pressure method. The test conditions are as follows: oxygen flow rate 0.2 mL / min, test temperature 25°C (room temperature), test time 4 hours. The oxygen permeability results (in cm 3 / m²·24h·0.1MPa) is used to evaluate the barrier properties of food packaging films. The lower the value, the better the barrier properties.
[0069] ⑥ Water barrier performance (water vapor transmission rate) test: Food packaging films prepared with different adhesive samples were cut into 15 mm wide experimental products to simulate the normal storage environment and the water vapor transmission rate was tested using the equilibrium method. The test conditions are as follows: test temperature 25°C (room temperature), humidity 50% RH, and test time 4 hours. The water barrier performance of the food packaging film is evaluated by the water vapor transmission rate results (in g / m²·24h). The lower the value, the better the barrier performance.
[0070] ⑦ Content resistance test: Each adhesive is coated on the surface of PET film or CPP film and aluminum foil respectively, and the structure of PET film + adhesive + aluminum foil + adhesive + CPP film is formed. After the adhesive is cured for 24 hours, the content resistance test is carried out. The sterilized food packaging bag is stored together with the fake food in a 40°C environment for 14 days, and the packaging bag remains unopened. After the storage period expires, the food packaging bag is cut open and the bonding condition between the PET film and the CPP film or aluminum foil is visually inspected to determine whether delamination (such as warping or peeling) occurs. The delamination is evaluated according to the delamination situation: excellent (no delamination), medium (slight delamination), poor (obvious delamination).
[0071] The test results are as follows:
[0072] The test results based on the above seven samples show that sample A and sample B performed the best overall, especially in terms of initial adhesion, adhesion strength, peel strength after sterilization, and oxygen and water vapor barrier properties. They show excellent performance and are suitable for application scenarios that require high adhesion of the packaging film and may undergo sterilization. They can also effectively block oxygen and water vapor to prevent food from being oxidized and deteriorated.
[0073] Samples D and E performed poorly in many tests, significantly lower than other samples. This may be due to the short reaction time resulting in insufficient cross-linking reaction and weak internal forces in the material.
[0074] The hard segment component in the control sample G was not added with grafted alumina, and the other preparation conditions were consistent with those of sample A. The results showed that the hard segment component was adjusted after adding grafted alumina, which greatly improved the various adhesion indicators and oxygen and water vapor barrier properties of the adhesive.
[0075] In general, the adhesive proposed by the present invention has significant advantages in multiple performance indicators, maintains strong initial adhesion and bonding strength after aging, has excellent peel strength after sterilization, and has a high barrier effect on oxygen and water vapor. By reasonably adjusting the viscosity of the adhesive solution and the coating process, the present invention can achieve precise control of food packaging needs and has high market application potential.
Claims
1. An adhesive for food packaging, characterized in that: The polyurethane comprises polyurethane, which is prepared by the following method: polyol, polyester and isocyanate components are mixed to undergo polymerization reaction, wherein the isocyanate component comprises hydroxyl-rich spherical aluminum oxide grafted with isocyanate groups.
2. The adhesive for food packaging according to claim 1, characterized in that: The spherical alumina grafted with isocyanate groups and rich in hydroxyl groups is spherical alumina grafted with 3-isocyanate propyltrimethoxysilane and rich in hydroxyl groups.
3. The adhesive for food packaging according to claim 2, characterized in that: The isocyanate-grafted hydroxyl-rich spherical alumina is prepared by the following method: (1) treating the spherical alumina with an alkali to obtain the hydroxyl-rich spherical alumina, wherein the alkali is NaOH or KOH; (2) reacting the hydroxyl-rich spherical alumina with a silyl-containing isocyanate to obtain the isocyanate-grafted hydroxyl-rich spherical alumina; the silyl-containing isocyanate is 3-isocyanatepropyltrimethoxysilane.
4. The adhesive for food packaging according to claim 1, characterized in that: The polyurethane further comprises a catalyst, and the catalyst is dimethylnitrosamine.
5. The adhesive for food packaging according to claim 1, characterized in that: The polyol is polyethylene glycol; and / or; the polyester is polycaprolactone; and / or; the isocyanate component is one or more of hexamethylene diisocyanate, toluene diisocyanate and hydroxyl-rich spherical alumina grafted with isocyanate groups.
6. The adhesive for food packaging according to claim 5, characterized in that: The isocyanate component is a mixture of hexamethylene diisocyanate, toluene diisocyanate and hydroxylated spherical alumina grafted with isocyanate groups.
7. The adhesive for food packaging according to claim 6, characterized in that: In the mixture, the mass ratio of the isocyanate components, namely, hexamethylene diisocyanate, toluene diisocyanate and spherical alumina rich in hydroxylation grafted with isocyanate groups, is (3-7): (3-7): 0.
5.
8. The adhesive for food packaging according to claim 1, characterized in that: The mass ratio of the polyol, the polyester and the isocyanate component is 10:(4-6):(0.8-1.2).
9. The adhesive for food packaging according to claim 8, characterized in that: The mass ratio of the polyol, the polyester and the isocyanate component is 10:5:
1.
10. Use of the adhesive for food packaging according to any one of claims 1 to 9 in food packaging bags.
Citation Information
Patent Citations
Adhesive for food packaging films
CN105829483A
Modified core-shell type aluminum oxide, polyurethane composite material, preparation methods and applications
CN110591158A
High-barrier weather-resistant thermal control polyurethane film and preparation method thereof
CN116063650A
Isocyanate composition, polyurethane adhesive and application thereof
CN117003984A
Detachable polyurethane heat-conducting structural adhesive and preparation method thereof
CN117487503A